Thin flexible structure with surface having transparent conductive film and method for forming structure
Thin flexible structures with transparent conductive films on both sides of a polymeric substrate address the limitations of ITO by offering flexible, durable, and efficient transparent conductive layers for electronic devices, particularly touch sensors, through roll-to-roll processing and UV-absorbing properties.
Patent Information
- Application Number
- JP2024174022
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-01-28
- Filing Date
- 2024-10-03
- Publication Date
- 2025-01-07
AI Technical Summary
Existing transparent conductive films, such as indium tin oxide (ITO), are brittle, require high-temperature vacuum deposition, and are not suitable for flexible and thin electronic devices, posing challenges for modern portable electronics.
Development of thin flexible structures with transparent conductive films on both sides of a polymeric substrate, using thinly spread metallic conductive layers and polymer overcoats, supported by a polymeric substrate with UV absorption properties, allowing for efficient roll-to-roll processing and patterning.
The solution provides flexible, thin, and durable transparent conductive structures with low sheet resistance, high transmittance, and low haze, suitable for touch sensors and other electronic devices, maintaining stability under accelerated wear tests and UV exposure.
Smart Images

Figure 2025000954000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a transparent structure having a transparent conductive surface suitable for incorporation into an electrical device having electrodes corresponding to a light transmitting or receiving structure, such as a transparent touch sensor. The transparent structure can have two transparent conductive surfaces on opposite sides of a thin substrate, such as a polyimide layer. The present invention further relates to a method for forming a thin flexible structure having a transparent conductive film, which can have a transparent conductive film on one or more surfaces of a thin flexible transparent layer. [Background technology]
[0002] Functional films can provide important functions in a variety of contexts. For example, electrically conductive films can be important for dissipation of static electricity when static electricity is undesirable or may be dangerous. Transparent conductive films can be used as electrodes. High quality displays can include one or more transparent conductive layers.
[0003] Transparent conductors can be used for several optoelectronic applications, such as touch screens, liquid crystal displays (LCDs), flat panel displays, organic light emitting diodes (OLEDs), solar cells, and smart windows. Traditionally, indium tin oxide (ITO) has been the preferred material due to its relatively high transparency at high electrical conductivity. However, there are several drawbacks with ITO. For example, ITO is a brittle ceramic that needs to be deposited using sputtering, a manufacturing method that requires high temperatures and vacuum and is therefore relatively time-consuming and not cost-effective. Furthermore, ITO is known to crack easily on flexible substrates. Newer portable electronic devices are scaling to thinner forms. Summary of the Invention [Means for solving the problem]
[0004] In a first aspect, the present invention relates to a double-sided conductive structure comprising a transparent polymer substrate, a thin metal conductive layer supported on each of a first surface and a second surface of the transparent polymer substrate, and a polymer overcoat on each thin metal conductive layer. In some embodiments, the transparent polymer substrate may comprise a polymer and have a first surface and a second surface, where the polymer substrate has an average thickness of about 27 microns or less, and the polymer in the form of the transparent polymer substrate has a transmittance of at least about 88% from 400 nm to 750 nm and a transmittance of about 15% or less across the UV spectrum from 330 nm to 375 nm. Typically, the polymer overcoat may have an average thickness of about 10 nm to about 200 nm. Each surface of the double-sided conductive structure may have a sheet resistance of about 120 Ohms / sq or less.
[0005] In a further aspect, the present invention relates to a method for forming a transparent conductive film, the method comprising: forming a thin, spread, metallic conductive layer supported on a first surface of a transparent polymeric substrate having an average thickness of about 27 microns or less, the polymeric substrate having a second surface supported on a first polymeric release film; applying a polymer overcoat over the first thin metallic conductive layer; placing a second polymeric release film over the polymeric overcoat; removing the first polymeric release film to expose a second surface of the transparent polymeric substrate; forming a second thin, spread-on metallic conductive layer supported on a second surface of the transparent polymeric substrate; applying a polymer overcoat over the second thin-film metal conductive layer.
[0006] In another aspect, the present invention relates to a transparent conductive film having an average thickness of about 30 microns or less, comprising a transparent polymer film having an average thickness of about 27 microns or less, a thinly spread metal conductive layer on each side of the transparent polymer film, and a polymer overcoat on each thinly spread metal conductive layer, the polymer overcoat having an average thickness of about 10 nm to about 500 nm. In some embodiments, the transparent conductive film has a sheet resistance of 100 Ohms / sq or less on each side, a %TT of at least 89%, a haze of 2.5% or less, and a b* of about 3.5 or less. In yet another or alternative embodiment, the double-sided conductive structure can be assembled into a test structure with an optically clear adhesive (3M, 8146) and a 125 micron thick PET film on each surface and subjected to an accelerated wear test at 85° C. and 85% relative humidity for 500 hours with an increase in sheet resistance of about 40% or less. [Brief description of the drawings]
[0007] [Figure 1] FIG. 1 is a schematic side view of a structure having two thin, spread-out metal conductive layers, one on either side of a thin polymer substrate. [Diagram 2] 2 is a schematic flow diagram of a process for forming the structure of FIG. 1. [Diagram 3] 1 is a simplified top view of a pattern of a touch sensor formed by a structure having two stacked patterned transparent conductive layers that form component electrodes of the touch sensor. [Figure 4] 1 is a schematic representation of roll-to-roll processing of the double-sided coated structures described herein. [Diagram 5] 1 is a flow diagram showing the roll-to-roll process used to coat a first side of the substrate used in the examples. [Figure 6] 1 is a flow diagram showing the roll-to-roll process used to coat the second side of the substrate used in the examples. [Figure 7]FIG. 1 is a schematic cross-sectional view showing a structure with two conductive surfaces and a hardcoat undercoat used for test specimens under 85C / 85%RH test conditions. [Figure 8] 8 is a plot of R / Ro as a function of time for the double-sided conductive structure of FIG. 7 using the first PI substrate subjected to an 85C / 85% RH accelerated wear test. [Figure 9] FIG. 1 is a schematic cross-sectional view of a structure used to perform Xe irradiation testing of conductive structures. [Figure 10] 10 is a plot of R / Ro as a function of time for the double-sided conductive structure shown in FIG. 9 under Xe test conditions using the first PI substrate. [Figure 11] FIG. 1 is a schematic cross-sectional view showing a structure having two conductive surfaces without a hardcoat undercoat used for test specimens under 85C / 85%RH test conditions. [Figure 12] 12 is a plot of R / Ro as a function of time for the double-sided conductive structure of FIG. 11 using the first PI substrate subjected to an 85C / 85% RH accelerated wear test. [Figure 13] FIG. 1 is a schematic cross-sectional view of a structure used to perform Xe irradiation testing of conductive structures. [Figure 14] FIG. 14 is a plot of R / Ro as a function of time for the double-sided conductive structure under the Xe test conditions shown in FIG. 13 using the first PI substrate. [Figure 15] FIG. 1 is a schematic cross-sectional view showing a structure with two conductive surfaces without a hardcoat undercoat used for test samples under 65C / 90%RH test conditions. [Figure 16] FIG. 1 is a schematic cross-sectional view of a structure used to perform Xe irradiation testing of conductive structures. [Figure 17] FIG. 16 is a plot of R / Ro as a function of time for the double-sided conductive structure of FIG. 15 using a second PI substrate subjected to a 65C / 90% RH accelerated wear test. [Figure 18]FIG. 17 is a plot of R / Ro as a function of time for the double-sided conductive structure under the Xe test conditions shown in FIG. 16 using the second PI substrate. [Figure 19] 8 is a plot of R / Ro as a function of time for the double-sided conductive structure of FIG. 7 using the first PI substrate subjected to a 65C / 90% RH accelerated wear test. [Figure 20] FIG. 10 is a plot of R / Ro as a function of time for the double-sided conductive structure under the Xe test conditions shown in FIG. 9 using the first PI substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Transparent conductive structures with particularly thin profile and suitable durability for electronic devices have been designed based on thin spread metal conductive layers on opposing sides of a thin transparent polymer substrate selected for specific properties. The transparent conductive structures can be useful for touch sensors. The selected polymer substrate can have a thickness of about 27 microns or less while providing good visible light transmittance and good UV absorption properties. The UV absorption properties provide independent UV-based patterning of conductive layers on both sides of the substrate. In some embodiments, flexible polymer substrates with a hard coat polymer protective barrier between the conductive layer and the polymer substrate provide particularly durable properties when evaluated using accelerated abrasion tests. Suitable processing methods have been developed that make handling of very thin substrates practical while performing coatings on both sides of the substrate. In processing, suitable protective polymer films can be used and removed at selected steps of the process to provide stable handling and protection of the precision structures. The design of double-sided coated structures can provide independent etching of each surface of the double-sided structure to introduce patterns based on, for example, the design of a touch sensor.
[0009] Transparent conductive films, typically based on indium tin oxide, are widely used for touch sensors or other components of electronic devices. Touch sensor designs typically include two electrically conductive elements. One conductive element can be used to reference one dimension in a plane, while a second element can be used to reference a second dimension in the plane and identify a touch point along the plane. Thus, to manufacture a touch sensor, typically two patterned conductive films are used, although additional transparent conductive layers can also be used. Generally, touch sensors can be relatively thin, but traditionally each electrically conductive element is associated with a separate substrate that is then assembled into a laminate. New products are creating a demand for thinner and / or more flexible structures. The ability to place both patterned conductive films on a single substrate allows for thinner and more flexible structures to be formed.
[0010] Being able to develop very thin sensor structures that are flexible can enable the technology of flexible electronics. For flexible devices with displays with touch sensors, the conductive elements are then transparent. Conventional conductive elements made from indium tin oxide and similar conductive ceramic oxides are not flexible. By using thin spread metallic conductive elements, flexible structures can be obtained. By placing two transparent conductive films on opposite sides of a single substrate, the thickness is reduced since only a single substrate is required. Also, very thin substrates suitable for this single substrate have been developed. New processing methods have been developed that allow for the efficient formation of this structure. Being able to form such structures with desirable optical and electronic properties at very small thicknesses poses significant challenges, which are met with the excellent results described herein.
[0011] Figure 1 shows the general structure of a double-sided conductive element in a unitary form on a core substrate. Referring to Figure 1, a double-sided conductive sheet 100 can include a substrate polymer sheet 102, an optional first hard coat 104, a first thin spread metal conductive layer 106, a first overcoat 108, an optional second hard coat 110, a second thin spread metal conductive layer 112, a second overcoat 114, an optional first peelable protective film 116, and an optional second peelable protective film 118. The properties of these materials are important to form a useful structure with suitable stability by suitable processing and for commercial use for electronic applications. The materials are described in detail below. The thin spread metal conductive layer can be effectively provided as a fused metal nanostructure network.
[0012] Formation of a touch sensor may require separate patterning of both conductive surfaces of a double-sided conductive structure. Typically, patterning of the conductive layer requires a patterning radiation source, such as a focused laser beam with laser ablation or irradiation through a mask with photolithography using a photoresist. While a variety of radiation sources can typically be used to perform the patterning, the desired patterning can be performed using an ultraviolet laser for ablation or a photoresist that is sensitive to ultraviolet light. For laser ablation, focused ultraviolet light, typically from an ultraviolet laser, can be scanned across the surface to define the pattern. For photolithography, ultraviolet light is directed through a mask to form a latent image in the photoresist, which is then developed to form the physical pattern. The physical pattern in the photoresist then provides a wet or dry etch that transfers the pattern to the thin metal conductive film. In both cases, the two thin metal conductive layers are typically patterned independently, since different patterns are required for the function of the touch sensor. For efficient processing, it is desirable for the two sides to be patterned such that the patterning on one side does not affect the other side.
[0013] To perform independent patterning of the two sides, for some embodiments, it may be desirable for the substrate to absorb ultraviolet light so that no significant ultraviolet light flux from one side reaches the other side, which can then alter the patterning of the opposing side. On the other hand, the substrate should have high transmittance of visible light. At the same time, the substrate should have suitable mechanical properties at the very small thickness required. Also, the absorption of high energy ultraviolet photons may tend to form reactive species depending on the nature of the ultraviolet absorbing composition. To have suitable durability, the thin spread metal conductive layer can protect the reactive species resulting from the patterning process from being damaged at all. As described herein, an optional hard coat can be disposed between the substrate and the thin spread metal conductive layer to protect the thin spread metal conductive layer. As demonstrated in the examples, the desired stability of the conductive layer can be achieved with or without the use of an optional hard coat.
[0014] To provide the desired UV absorption capability while maintaining high visible light transmittance and mechanical durability at the desired small thickness, a polyimide substrate is exemplified below, although other polymer substrates may be used. A polyimide substrate may be selected to provide good transmittance across the visible spectrum while having strong UV absorption. Other polymers besides polyimide with the desired properties are identified below. Processing to form conductive structures may be performed in a commercial roll-to-roll process or similar processing method to form the structures. The desired structures are very thin, but processing methods have been developed to allow for proper processing.
[0015] The structures described herein avoid using polymers with additives in the polymer to absorb UV light or using a separate layer solely to absorb UV light. Thus, the structures herein can maintain a high degree of mechanical stability and stability during use of the conductive layer. The engineering of the structures described herein provides excellent performance in a very thin form factor suitable for foldable touch screen products. Polymers such as polyimide with suitable optical properties can provide high mechanical strength while providing high flexibility.
[0016] Other transparent double-sided conductive structures have been described in the art. The general patterning of two sides of a transparent substrate with conductive layers is described in U.S. Patent No. 9,292,141 to Zhong et al. (hereinafter the '141 patent) entitled "Double Sided Touch Sensor on Transparent Substrate" (herein incorporated by reference). The '141 patent focuses primarily on transparent conductive films based on conductive oxides such as ITO, which refers to transparent conductive films more generally. Double-sided patterning of a substrate with a nanowire-based conductive layer is described in U.S. Patent Application Publication No. 2014 / 0202742 to Jones et al. (hereinafter the '742 application) entitled "Two-Sided Laser Patterning on Thin Film Substrates" (herein incorporated by reference). The '141 patent and the '742 application do not teach the structures described herein having the improved mechanical and optical properties based on material engineering techniques and enabled by the processing methods described herein.
[0017] Various accelerated abrasion tests have been developed to test the durability of transparent conductive films for commercial evaluation. The following examples provide tests of double-sided transparent conductive films formed as described herein. Some of these accelerated abrasion tests are similar with slight variations that make the tests more or less stringent. These tests are widely accepted in the industry for testing purposes.
[0018] To provide stable processing of thin double-sided conductive structures, the film can be processed using a stabilizing peelable polymer carrier film during the coating process. At the end of processing, the final film can be covered on both sides by a polymer release layer that can protect the film during shipping or storage if further processing is performed at a time interval. In general, the various processing steps can be influenced by the order of processing and the location of processing. For practical commercial applications, the double-sided conductive film can be processed in one location and shipped for patterning and additional processing into a touch sensor, but essentially the processing can be performed in a single physical location.
[0019] With a polymer substrate supported by a peelable polymer carrier film, one side of the substrate can be processed to provide an undercoat, a conductive layer with thinly spread metallic conductive structures, and an overcoat layer. The dried overcoat can be covered with a polymer release layer, and then the first peelable polymer carrier layer can be removed to expose the other side of the substrate, with the polymer sheet on the overcoat of the first side serving as a carrier layer for processing of the second side. The undercoat, the conductive layer with thinly spread metallic conductive structures, and the overcoat are applied to the second side of the substrate, and the substrate is generally placed upside down against the process equipment, with the side to be processed facing up. If necessary, another peelable polymer sheet can be placed on top of the dried overcoat of the second processed side to complete the structure, and stored and / or transported. Various more specific embodiments are discussed below.
[0020] The processing improvements and material engineering techniques described herein allow for the use of very thin substrates while providing and patterning two opposing conductive surfaces. Thus, in some embodiments, the finished structure can have a total thickness, including substrate, two conductive layers, undercoat, and overcoat, of about 35 microns or less. The sheet resistance of each of the opposing layers can be about 100 Ohms / sq or less. The resulting double-sided conductive structure can have a total transmission of visible light of at least about 85%, a haze of about 2.5% or less, and a b* value of about 4 or less. These properties can be maintained while the entire structure can be very flexible, which is further facilitated by the thinness. Thus, the double-sided conductive structure herein is particularly suitable for forming transparent touch sensors for flexible electronic devices.
[0021] The basic processing method involving the use of a peelable carrier film for handling very thin structures is illustrated diagrammatically in FIG. 2, showing the general process flow. At the start of the illustrated flow, a thin substrate 140 is provided with a first peelable carrier layer 142. The first peelable carrier layer 142 covers one surface of the structure, and the other surface is processed 144 to form a first transparent conductive coating 146 having a thin spread metallic conductive layer and any associated layers. After processing is completed on the first side, a second peelable carrier layer 150 is placed 152 on top of the conductive coating 146. With the structure supported by the second peelable carrier layer 150, the first peelable carrier layer 142 on the other surface is removed 154 to expose a raw surface 156 of the thin substrate 140. It can be optionally flipped 158 in space so that the raw surface is facing up for ease of processing. The other side of the thin substrate 140 is then correspondingly processed 160 to form a second transparent conductive coating 162 on the second side of the substrate 140, where the second transparent conductive coating 162 generally comprises a thin spread metal conductive layer and any associated layers. A top peelable carrier film 164 may be placed 166 over the second transparent conductive coating 162 to protect the second transparent conductive coating 162 prior to patterning or other further processing. In some embodiments, the completed structure may be rolled up for shipping and / or storage if necessary.
[0022] The process for forming the transparent conductive layer generally includes deposition of a nanowire ink, drying of the nanowire ink (which can result in fusing to form a fused metal nanostructure network), deposition of an overcoat, and drying and curing of the overcoat. The process can further include deposition of an optional hardcoat as an undercoat between the substrate and the thin-spread metal conductive layer. As an underlayer, the hardcoat may not provide mechanical protection, but the hardcoat can provide stability to the thin-spread metal conductive layer, possibly from process damage or other interactions from the substrate. The hardcoat is generally transparent to both visible and near-ultraviolet light.
[0023] In general, various thin, spread metal conductive layers can be formed from metal nanowires. Films formed from metal nanowires and processed to flatten the nanowires at the junctions to improve electrical conductivity are described in U.S. Patent No. 8,049,333 to Alden et al., entitled "Transparent Conductors Comprising Metal Nanowires," which is incorporated herein by reference. Structures including metal nanowires embedded in the surface to increase metal conductivity are described in U.S. Patent No. 8,748,749 to Srinivas et al., entitled "Patterned Transparent Conductors and Related Manufacturing Methods," which is incorporated herein by reference. However, improved properties in terms of high electrical conductivity and desirable optical properties in terms of transparency and low haze have been found for fused metal nanostructure networks. The fusion of adjacent metal nanowires can be carried out based on chemical processes under commercially suitable processing conditions.
[0024] In particular, a significant advance in achieving metal nanowire-based electrically conductive films was the discovery of a well-controllable method to form a fused metal network in which adjacent portions of metal nanowires fuse together to form a monolithic structure with no separate nanowires in the conductive network. In particular, it was first discovered that halide ions can induce the fusion of metal nanowires to form fused metal nanostructures. A flux containing halide anions was introduced in various ways to successfully achieve fusion, with a corresponding significant reduction in electrical resistance. It should be noted that halide ions in this processing context should not be confused with halide ions used in nanowire synthesis reactions. Specifically, fusion of metal nanowires using halide anions has been achieved using acid halide vapors and / or solutions, as well as solutions of halide salts. Fusion bonding of metal nanowires using halide sources is further described in U.S. Pat. No. 10,029,916 to Virkar et al., entitled "Metal Nanowire Networks and Transparent Conductive Material," and U.S. Pat. No. 9,920,207 to Virkar et al., entitled "Metal Nanostructured Networks and Transparent Conductive Material" (the '207 patent), both of which are incorporated herein by reference.
[0025] Methods developed for forming fused metal nanowire networks have been based on reduction / oxidation (redox) reactions, which can be provided to result in fused nanowires without compromising the optical properties of the resulting film. The metal for deposition at the junctions can be usefully added as dissolved metal salts or dissolved from the metal nanowires themselves. The useful use of redox chemistry to fuse metal nanowires to form nanostructured networks is further described in U.S. Pat. No. 10,020,807 (the '807 patent) to Virkar et al., entitled "Fused Metal Nanostructured Networks, Fusing Solutions with Reducing Agents and Methods for Forming Metal Networks," which is incorporated herein by reference. The '807 patent also describes a single solution approach for the formation of fused metal nanostructured networks. A single solution approach for the formation of fused metal nanostructured layers is further described in U.S. Pat. No. 9,183,968 B1 to Li et al. (hereinafter the '968 patent), entitled "Metal Nanowire Inks for the Formation of Transparent Conductive Films with Fused Networks," which is incorporated herein by reference, and a single solution or ink process for forming fused metal nanostructured networks is used in the examples below.
[0026] The desired ink contains the desired amount of metal nanowires to achieve an effective single deposition ink that cures into a fused nanostructured metal network to achieve the proper loading of metal in the resulting film. In the appropriate solution, the ink is stable prior to ink deposition and drying. The ink can contain a moderate amount of polymer binder that contributes to the formation of a stable conductive film for further processing. To obtain good fusing results with a single ink system, hydrophilic polymers such as cellulose or chitosan-based polymers have been found to be effective. Metal ions as a source of metal for the fusing process can be provided as soluble metal salts.
[0027] The single ink formulation provides components in the ink that deposit the desired loading of metal as a film on the substrate surface while simultaneously inducing the fusion process when the ink is dried under appropriate conditions. These inks may be conveniently referred to as fusion metal nanowire inks, with the understanding that fusion does not generally occur until dry. The ink typically includes an aqueous solvent, which in some embodiments may further include alcohol and / or other organic solvents. The ink may further include dissolved metal salts as a source of metal for the fusion process. Without wishing to be limited by theory, it is believed that components of the ink, such as alcohol or other organic compositions, reduce metal ions out of solution to induce the fusion process. Previous experience with the fusion process in these systems suggests that the metal preferentially deposits at the junctions between adjacent metal nanowires. A polymer binder may be provided to stabilize the film and affect the ink properties. The specific formulation of the ink may be adjusted to select ink properties that are suitable for a particular deposition method and have a particular coatability on the substrate surface. As further described below, drying conditions may be selected to effectively effect the fusion process. Additionally, two solution fusion systems have been established that can utilize the improved silver nanowires described herein.
[0028] The double-sided conductive film can be appropriately patterned for incorporation into devices such as touch sensors. For patterning, any protective release layer can be removed to expose the overcoat. The overcoat is thin, and patterning generally required corresponding patterning of the overcoat with the conductive layer. The patterned film can be cut to the desired size. For assembly into a device, an optically transparent adhesive can be applied to the patterned conductive film to attach the film to the device. The transparent conductive structures can be connected to metal traces along the edges of the film to incorporate the transparent conductors into the circuit. Another portion of the optically transparent adhesive can provide a protective covering for the device, which can be a flexible polymer sheet for desired flexible devices. The thin flexibility of the double-sided coated structures described herein provides a significant advancement for certain device applications.
[0029] Double-sided, separately patternable electrically conductive structures The electrically conductive structures herein include electrically conductive layers on opposing surfaces that can provide distinct conductive features for integration into electrical devices, such as touch sensors. The substrate is selected to have good transmission of visible light and good absorption of ultraviolet light. Suitable polymers are described that can have high durability and mechanical properties at small thicknesses suitable for flexible structures. The structures can also have good stability of electrical conductivity under accelerated wear test conditions at high temperature and humidity levels. In some embodiments, the entire structure, including the protective polymer overcoat, can have an overall average thickness of about 30 microns or less, which is desirable for forming thinner final products with suitable mechanical properties as well as flexible displays. The double-sided conductive structures described herein have achieved suitable flexibility for commercial levels of foldable electronics assembled into practical display devices, and based on testing for these applications, double-sided conductive structures with overcoats on both surfaces can be repeatedly bent at least 200,000 times around a 1 mm diameter mandrel, and the sheet resistance of the conductive surface changes by 10% or less. Experience strongly suggests that such bending can be performed for at least millions of bends.
[0030] The basic structure is shown in FIG. 1 above. The polymer substrate is the core of the structure, both literally since the conductive layers are applied on both sides, and in a sense figuratively since it is the majority of the thickness of the structure. The polymer comprises, as the major component, generally at least 50 weight percent of the polymer, which is referred to as the substrate polymer. A suitable substrate polymer is transparent to visible light. Specifically, the transmittance of the substrate polymer is generally at least about 88%, in some embodiments at least about 89%, in yet other embodiments at least about 90% and in further embodiments at least about 91%. The optical properties and measurements of the optical properties of the entire structure are discussed in more detail below, and the related general discussion provided in more detail below applies here as well. Also, for the selected thickness of the substrate (transmittance properties are thickness dependent), the substrate polymer absorbs ultraviolet light having a wavelength of 330 nm to 370 nm, and thus the transmittance over this wavelength range is about 15% or less, in further embodiments about 10% or less, in yet other embodiments about 5% or less, and in other embodiments about 2% or less. The polymeric substrate can generally have an average thickness of about 27 microns or less, in further embodiments from about 1 micron to about 25 microns, and in other embodiments from about 5 microns to about 23 microns, although useful substrates in some embodiments can have a thickness of about 5 microns to about 60 microns. A person of ordinary skill in the art will recognize that additional ranges of transmittance and thickness within the explicit ranges above are contemplated and are within the scope of the present disclosure.
[0031] Suitable polymers include, for example, polyimides, polysulfides (e.g., Pylux™, Ares Materials), polysulfones (e.g., Udel® from Solvay), or polyethersulfones (e.g., Veradel® from Solvay or Ultrason® from BASF), and polyethylene naphthalates (e.g., Teonex® from DuPont). Examples are given below based on transparent polyimides. Conventional aromatic polyimides are colored. However, recently developed polyimides are transparent to visible light. Transparent polyimides absorb ultraviolet light. Transparent polyimides are available from Kolon (Korea), Taimide Tech. (Taiwan), Sumitomo (Japan), SKC Inc. (GA, USA) and NeXolve (AL, USA).
[0032] The use of a base polymer that itself absorbs ultraviolet light avoids the use of a separate layer of either an ultraviolet absorber or a UV filler in the polymer. The use of a separate layer of ultraviolet absorber would increase the thickness of the structure and alter the mechanical properties. The use of an ultraviolet absorber as a filler in the polymer substrate may alter the mechanical and chemical properties of the polymer substrate. The structures herein rely on the ultraviolet absorbing properties of the substrate polymer to achieve the highly desirable properties of the structure. The use of polyesters with ultraviolet absorbing fillers has been suggested. See US Patent Application Publication No. 2014 / 0202742 to Jones et al., entitled "Two-Sided Laser Patterning on Thin Film Substrates," incorporated herein by reference. The use of fillers may alter stability and mechanical properties.
[0033] For use in flexible displays, it is desirable for the polymer substrate to have desirable mechanical properties. The durability of the material can be expressed in some sense by elongation, which is a measure of the extent to which the material can be stretched without breaking, and / or by tensile strength, which is a measure of the force that can be applied until the material fails. Elongation is typically provided by the polymer manufacturer as measured by a standardized procedure, typically AS™ D882. In some embodiments, it is desirable for the elongation to be at least about 10%, in further embodiments at least about 15%, and in other embodiments from about 20% to about 100%. In some embodiments, the tensile strength of the substrate can be at least about 50 MPa, in further embodiments at least about 60 MPa, and in some embodiments from about 65 MPa to about 300 MPa. Also, for some applications, the (Young's) modulus of elasticity of the substrate polymer can be from about 1.5 GPa to about 7.0 GPa, in further embodiments from about 1.75 GPa to about 6.5 GPa, and in other embodiments from about 2.0 GPa to about 6 GPa. A person of ordinary skill in the art will recognize that additional ranges of elongation, tensile strength, and modulus within the explicit ranges above are contemplated and are within the present disclosure.
[0034] Electrical conductivity on the two faces of the structure is provided by thinly spread metal conductive layers. Thinly spread metal conductive layers are discussed in more detail in the following section. Generally, the thickness of these layers is very small, since the nanowires may be on the order of 10-25 nanometers (nm) thick, and somewhat thinner nanowires may be available in the future. The thinly spread metal conductive layers may be fused metal nanostructured networks formed by fusing initially deposited metal nanowires to a unitary transparent metal structure. Following the applicant's work, fused metal nanostructured networks have been studied by Academic Research Laboratories. The bending stability of transparent conductive layers on polymer substrates has been evaluated. See Cheng et al., “Highly foldable transparent conductive films composed of silver nanowire junctions prepared by chemical metal reduction, Nanotechnology 25 (2014) 285601 (page 7) (hereafter Cheng et al.). Using a less desirable technique for fused silver nanowires, it was found that fusion nevertheless provides significant bending stability to the resulting transparent conductive film. Specifically, Cheng et al. determined that the fused metal nanostructured network was much more stable in structures that were repeatedly bent versus corresponding structures that were not fused. The use of fused metal nanostructured networks is believed to be important for obtaining structures with long-term use stability for flexible displays.
[0035] The thin metal conductive layer is typically covered with a polymer overcoat to provide mechanical protection for the conductive layer. In some embodiments, it may be possible to select the overcoat to significantly reduce haze after application of the overcoat without significantly degrading other properties. Also, the thickness and composition of the overcoat may be selected such that measurements of the sheet resistance of the overcoat are not significantly altered relative to measurements without the overcoat. Suitable commercial coating compositions for the overcoat include, for example, coating solutions POSS® Coatings from Hybrid Plastics, Inc. (Mississippi, USA), silica-filled siloxane coatings from California Hardcoating Company (California, USA), Acier® Hybrid Hard Coating Material from Nidek (Japan), SK1100 series hardcoats from Dexerials Corporation (Japan), Lioduras™ from Toyochem (Japan), HC-5619 hardcoat from Addison Clear Wave (IL, USA), and CrystalCoat UV-curable coatings from SDC Technologies, Inc. (California, USA). The incorporation of stabilizers into the overcoat is described in pending U.S. patent application Ser. No. 15 / 730,053 to Yang et al., entitled "Stabilized Sparse Metal Conductive Films and Solutions for Delivery of Stabilizing Compounds," which is incorporated herein by reference.
[0036] Although the overcoat polymer is generally dielectric, the overcoat layers, one on each of the two thinly spread metal conductive layers, are generally thin enough to allow electrical conductivity in the overcoat. In other words, a surface having an overcoat should generally have about the same sheet resistance as a surface without the overcoat. Thus, it may be desirable for the polymer overcoat to have an average thickness of about 250 nm or less, in some embodiments from about 5 nm to about 200 nm, and in further embodiments from about 10 nm to about 175 nm. A person of ordinary skill in the art will recognize that additional ranges of thickness within the above explicit ranges are contemplated and are within the scope of the present disclosure.
[0037] As mentioned above, the conductive structure can include an underlayer between the polymer substrate and the thinly spread metal conductive layer. The underlayer can include a polymer hardcoat. As an underlayer, the polymer hardcoat does not provide mechanical protection, but the polymer hardcoat can provide protection from chemical attack. As explained in the examples, the polymer hardcoat underlayer provides significant stability to the fused metal nanostructure layer for some polymer substrates, but for some similar thicker substrates, no undercoat is used to obtain good stability. It is not yet understood why some structures are stable enough without a hardcoat.
[0038] Suitable hardcoat polymers are generally highly crosslinked polymers having crosslinked polyacrylates that may be combined with other crosslinked moieties such as polyurethanes, epoxy polymers, polysiloxanes, and / or other crosslinked polymers. Branched acrylate monomers may result in the formation of highly crosslinked polymers, and crosslinked acrylates may be copolymerized with other moieties such as urethane acrylates to form interlocked crosslinked polymers. Hardcoat polymers are commercially available, such as coating solutions from POSS® Coatings from Hybrid Plastics, Inc. (Mississippi, USA), silica-filled siloxane coatings from California Hardcoating Company (California, USA), Acier® hybrid hardcoat materials from Nidek (Japan), SK1100 series hardcoats from Dexerials Corporation (Japan), Lioduras™ from Toyochem (Japan), HC-5619 hardcoat from Addison Clear Wave (IL, USA), and CrystalCoat UV-curable coatings from SDC Technologies, Inc. (California, USA). Hardcoat polymers are further described in U.S. Patent Application Publication No. 2016 / 0369104 to Gu et al., entitled “Transparent Polymer Hardcoats and Corresponding Transparent Films,” which is incorporated herein by reference.
[0039] Suitable hardcoat polymers are available that are highly transparent for the relevant thickness, and the hardcoat does not significantly reduce the transmission of light through the structure. The polymer hardcoat layers can each independently have an average thickness of from about 250 nm to about 4 microns, in further embodiments from about 400 nm to about 3.5 microns, and in other embodiments from about 500 nm to about 3 microns. A person of ordinary skill in the art will recognize that additional ranges of hardcoat thickness within the above explicit ranges are contemplated and are within the scope of the present disclosure.
[0040] The final structure has a crosslinked overcoat layer on each surface, each providing a relatively non-tacky surface. To protect the structure for shipping, storage, etc., one or both surfaces may be protected with a peelable polymer layer. The peelable polymer layer may be formed to have a thickness of about 15 microns to about 200 microns, in further embodiments about 20 microns to about 180 microns, in other embodiments about 25 microns to about 170 microns, and in yet other embodiments about 40 microns to about 150 microns. Those skilled in the art will recognize that additional ranges of thickness within the above stated ranges are contemplated and within the scope of the present disclosure. A wide variety of suitable non-tacky polymers may be used for the polymeric release layer, and optical properties are not an issue since the release layer is removed for further processing. Suitable polymers include, for example, polyethylene, polypropylene, polyester, polyamide, polysiloxane, copolymers thereof, and the like. The particular polymer may be selected to have low tack, and the peel strength of such a release layer may be low enough so that the material is not damaged when the release layer is peeled from the substrate.
[0041] A thin conductive metal layer The thin metal conductive layer is generally formed from metal nanowires. With sufficient loading and selected nanowire properties, it is possible to achieve a reasonable electrical conductivity using nanowires with corresponding suitable optical properties. It is expected that transparent conductive film structures formed using silver nanowires can provide desirable performance for double-sided conductive films with structures described herein having various thin metal conductive structures. However, particularly desirable properties have been achieved with fused metal nanostructure networks. The discussion herein focuses on embodiments that include fused metal nanostructure networks that have been found to provide improved performance properties as transparent conductive films.
[0042] Several practical methods have been developed to perform metal nanowire fusion. Metal loading can be balanced to achieve the desired level of electrical conductivity with good optical properties. In general, metal nanowire fabrication can be achieved by two-ink deposition, with a first ink containing metal nanowires and a second ink containing a fusion composition, or by ink deposition that mixes fusion elements into a metal nanowire dispersion. The ink may or may not contain additional processing aids, binders, etc. A suitable patterning method can be selected as appropriate for a particular ink system.
[0043] In general, one or more solutions or inks for the formation of metal nanostructured networks can collectively include well-dispersed metal nanowires, a flux, and optional further components, such as polymer binders, crosslinkers, wetting agents, such as surfactants, thickeners, dispersants, other optional additives, or combinations thereof. The solvent for the metal nanowire ink and / or fusing solution, if different from the nanowire ink, can include aqueous solvents, organic solvents, or mixtures thereof. In particular, suitable solvents include, for example, water, alcohols, ketones, esters, ethers, such as glycol ethers, aromatics, alkanes, and the like, and mixtures thereof. Specific solvents include, for example, water, ethanol, isopropyl alcohol, isobutyl alcohol, tertiary butyl alcohol, methyl ethyl ketone, glycol ethers, methyl isobutyl ketone, toluene, hexane, ethyl acetate, butyl acetate, ethyl lactate, PGMEA (2-methoxy-1-methylethyl acetate), dimethyl carbonate, or mixtures thereof. The solvent may be selected based on its ability to form a good dispersion of the metal nanowires, but also should be compatible with the other selected additives such that the additives are soluble in the solvent. For embodiments in which the flux is contained in a single solution with the metal nanowires, the solvent or a component thereof may or may not be a significant component of the fusing solution, such as an alcohol, and may be selected accordingly, if necessary.
[0044] The metal nanowire ink, in either a one-ink or two-ink configuration, can contain from about 0.01 to about 1 weight percent metal nanowires, in further embodiments from about 0.02 to about 0.75 weight percent metal nanowires, and in yet other embodiments from about 0.04 to about 0.5 weight percent metal nanowires. A person of ordinary skill in the art will appreciate that additional ranges of metal nanowire concentrations within the explicit ranges above are contemplated and are within the scope of the present disclosure. The concentration of metal nanowires affects the loading of metal on the substrate surface as well as the physical properties of the ink.
[0045] Silver provides excellent electrical conductivity. Applicant sells a suitable silver nanowire ink for forming a fused metallic nanostructure network under the trade name Activegrid™ ink. Other sources of silver nanowires are commercially available, and the basic fusion techniques are fully described in the '207 and '807 patents referenced above.
[0046] The polymeric binder and the solvent are generally selected so that the polymeric binder is soluble or dispersible in the solvent. In suitable embodiments, the metal nanowire ink generally comprises about 0.02 to about 5 weight percent of the binder, in further embodiments about 0.05 to about 4 weight percent of the binder, and in yet other embodiments about 0.1 to about 2.5 weight percent of the polymeric binder. In some embodiments, the polymeric binder comprises a crosslinkable organic polymer, such as a radiation crosslinkable organic polymer and / or a thermosetting organic binder. To facilitate crosslinking of the binder, the metal nanowire ink can comprise about 0.0005 wt % to about 1 wt % of a crosslinker in some embodiments, about 0.002 wt % to about 0.5 wt % in further embodiments, and about 0.005 wt % to about 0.25 wt % in yet other embodiments. The nanowire ink can optionally comprise a rheology modifier or combinations thereof. In some embodiments, the ink can comprise a wetting agent or surfactant to reduce surface tension, and wetting agents can be useful for improving coatability. The humectant is generally soluble in the solvent. In some embodiments, the nanowire ink can include from about 0.001 weight percent to about 1 weight percent humectant, in further embodiments from about 0.002 to about 0.75 weight percent, and in other embodiments from about 0.003 to about 0.6 weight percent humectant. A thickener can optionally be used as a rheology modifier to stabilize the dispersion and reduce or eliminate settling. In some embodiments, the nanowire ink can optionally include from about 0.05 to about 5 weight percent thickener, in further embodiments from about 0.075 to about 4 weight percent, and in other embodiments from about 0.1 to about 3 weight percent thickener. A person of ordinary skill in the art will recognize that additional ranges of binder, humectant, and thickener concentrations within the above explicit ranges are contemplated and are within the scope of the present disclosure.
[0047] A wide range of polymer binders may be suitable for dissolving / dispersing in a solvent for metal nanowires, but suitable binders include polymers developed for coating applications. Hard coat polymers, e.g., radiation curable coatings, may be selected to dissolve in aqueous or non-aqueous solvents, e.g., are commercially available as hard coat materials for a wide range of applications. Suitable types of radiation curable and / or thermosetting polymers include, for example, polyurethanes, acrylic resins, acrylic copolymers, cellulose ethers and esters, other water-insoluble structural polysaccharides, polyethers, polyesters, epoxy-containing polymers, and mixtures thereof. Examples of commercial polymer binders include, for example, NEOCRYL® brand acrylic resins (DMS NeoResins), JONCRYL® brand acrylic copolymers (BASF Resins), ELVACITE® brand acrylic resins (Lucite International), SANCURE® brand urethanes (Lubrizol Advanced Materials), cellulose acetobutyrate polymers (CAB brand from Eastman™ Chemical), BAYHYDROL® brand polyurethane dispersions (Bayer Material Science), UCECOAT® brand polyurethane dispersions (Cytec Industries, Inc.), MOWITOL® brand polyvinyl butyrals (Kuraray America, Inc.), cellulose ethers such as ethyl cellulose or hydroxypropyl methylcellulose, other polysaccharide-based polymers such as chitosan and pectin, synthetic polymers such as polyvinyl acetate, and the like. In particular, polysaccharide-based polymers have been found to be desirable as binders in thinly spread metal conductive layers. The polymer binders may be self-crosslinkable upon exposure to radiation, and / or they may be crosslinked by photoinitiators or other crosslinking agents. In some embodiments, photocrosslinkers may form radicals upon exposure to radiation, which then initiate a crosslinking reaction based on a radical polymerization mechanism.Suitable photoinitiators include, for example, commercially available products such as IRGACURE® brands (BASF), GENOCURE™ brands (RahnUSA Corp.), and DOUBLECURE® brands (Double Bond Chemical Ind., Co, Ltd.), combinations thereof, and the like.
[0048] Wetting agents can be used to improve the coverage of metal nanowire inks as well as the quality of metal nanowire dispersions. In particular, wetting agents can reduce the surface energy of the ink so that the ink spreads well on the surface after coating. Wetting agents can be surfactants and / or dispersants. Surfactants are a class of materials that function to reduce surface energy, and surfactants can improve the solubility of materials. Surfactants generally have a hydrophilic portion of the molecule that contributes to their properties and a hydrophobic portion of the molecule. A wide range of surfactants are commercially available, including nonionic, cationic, anionic, and zwitterionic surfactants. In some embodiments, when the properties associated with surfactants are not an issue, non-surfactant wetting agents, such as dispersants, are also known in the art and can be effective to improve the wetting ability of the ink. Suitable commercial wetting agents include, for example, COATOSIL™ brand epoxy functionalized silane oligomers (Momentum Performance Materials), SILWET™ brand organosilicone surfactants (Momentum Performance Materials), THETAWET™ brand short chain nonionic fluorosurfactants (ICT Industries, Inc.), ZETASPERSE™ brand polymeric dispersants (Air Products Inc.), SOLSPERSE™ brand polymeric dispersants (Lubrizol), Capstone™ fluorosurfactants (DuPont™), XOANONS WE-D545 surfactant (Anhui Xoanons Chemical Co., Ltd.), EFKA™ PU 4009 polymeric dispersant (BASF), MASURF FP-815 CP, MASURF FS-910 (Mason Chemicals), NOVEC™ FC-4430 fluorinated surfactant (3M), mixtures thereof, and the like.
[0049] Thickeners can be used to improve dispersion stability by reducing or eliminating settling of solids from the metal nanowire ink, and may or may not significantly change the viscosity or other fluid properties of the ink. Suitable thickeners are commercially available and include, for example, CRAYVALLAC™ brand modified ureas such as LA-100 (Cray Valley Acrylics, USA), polyacrylamides, THIXOL™ 53L brand acrylic thickeners, COAPUR™ 2025, COAPUR™ 830W, COAPUR™ 6050, COAPUR™ XS71 (Coatex, Inc.), BYK™ brand modified ureas (BYK Additives), Acrysol DR73, Acrysol RM-995, Acrysol RM-8W (Dow Coating Materials), Aquaflow NHS-300, Aquaflow XLS-530 hydrophobically modified polyether thickeners (Ashland Inc.), Borchi Gel L 75N, Borchi Gel PW25 (OMG Borchers), and the like.
[0050] Additional additives can be added to the metal nanowire ink generally in an amount of about 5 weight percent or less each, in further embodiments about 2 weight percent or less, and in further embodiments about 1 weight percent or less. Other additives can include, for example, antioxidants, UV stabilizers, defoamers or antifoamers, anti-settling agents, viscosity modifiers, and the like.
[0051] The process for forming the deposited metal nanostructured layer is described below.
[0052] Optical and electrical properties of double-sided structures Transparent structures having a thinly spread metal conductive layer, for example a double-sided conductive film incorporating a fused metal nanostructure network, can provide low electrical resistance while providing good optical properties. Thus, the film can be useful as a transparent conductive electrode or the like. Transparent conductive electrodes can be suitable for a variety of applications. For displays and especially for touch screens, the film can be patterned separately on each side to provide an electrically conductive pattern formed by the film. Double-sided conductive structures generally have good optical properties with high transmittance, low haze and low color.
[0053] The electrical resistance of a thin film can be expressed as sheet resistance, which is reported in units of ohms per square (Ω / □ or ohms / sq), and is distinguished from bulk electrical resistance values according to parameters related to the measurement method. The sheet resistance of a film is typically measured using a four-point probe measurement or another suitable method. In some embodiments, each conductive surface of the structure can have a sheet resistance of about 200 ohms / sq or less, in further embodiments about 150 ohms / sq or less, in yet other embodiments about 100 ohms / sq or less, and in other embodiments about 75 ohms / sq or less. Those of skill in the art will appreciate that additional ranges of sheet resistance within the above stated ranges are contemplated and are within the scope of the present disclosure. In the examples, a transparent conductive film is formed having a target sheet resistance of 50 ohms / sq. Generally, the sheet resistance can be reduced by increasing the loading of nanowires, although increased loading may or may not be desirable from other perspectives.
[0054] For applications as transparent conductive films, it is desirable for a fused metal nanowire network or other thinly spread metal conductive layer to maintain good optical transparency. Essentially, optical transparency is inversely proportional to metal loading, with higher loadings resulting in decreased transparency, but processing of the network can also affect transparency significantly. Polymer binders and other additives can also be selected to maintain good optical transparency. Transparency can be reported using a dimensionless quantity, transmittance. Transmittance is the ratio of the intensity of transmitted light (I) to the intensity of incident light (I o ) is the ratio of the transmittance to the total transmittance of the conductive layer. The transmittance is reported in the examples below for the transparent conductive layer in a double-sided conductive structure with an overcoat layer. The optical transmittance of the transparent conductive layer can be evaluated for light transmitted through a substrate supporting the transparent conductive film. For example, the transparency of the conductive layer described herein can be measured using a UV-Vis spectrophotometer to measure the total transmittance through the conductive layer and the supporting substrate. The transmittance values are reported for the transparent conductive layer on a transparent film substrate. The transmittance through a single layer can be estimated, if necessary, by measuring various intermediates based on the total transmittance, which is approximately the product of the individual transmittances.
[0055] Although it is generally desirable to have good optical transparency across the visible spectrum, for convenience, the optical transmission can be reported at a wavelength of 550 nm. Alternatively or additionally, the transmission can be reported as the total transmittance of light from 400 nm to 700 nm, and such results are reported in the Examples below. In general, for bonded metal nanowire films, the measurements of the transmittance at 550 nm and the total transmittance (or simply "total transmittance" for convenience) from 400 nm to 700 nm are not qualitatively different. In some embodiments, the double-sided conductive structure has a total transmittance (TT%) of at least 85%, in further embodiments at least about 88%, in yet other embodiments at least about 89%, in other embodiments from about 90% to about 96%, and in some embodiments from about 90.5% to about 95%. The transmittance of the film can be evaluated using standard ASTM D1003 ("Standard Test Method for Haze and Luminous Transmittance of Transparent Plastics"), which is incorporated herein by reference. A person of ordinary skill in the art will recognize that additional ranges of transmittance within the explicit ranges above are contemplated and are within the present disclosure.
[0056] The fused metal network can also have low haze with high transmission of visible light while desirably having low sheet resistance. Haze can be measured using a haze meter according to ASTM D1003 referenced above, and the haze contribution of the substrate can be removed to provide a haze value for the transparent conductive film. Haze measured according to ASTM D1003 is haze based on transmission, and a separate measurement can be made for haze based on reflection. Unless expressly indicated otherwise, haze refers to haze based on transmission. In some embodiments, the transparent conductive film can have a haze value of about 2.5% or less, in further embodiments about 2.25% or less, in yet other embodiments about 2.0% or less, and in other embodiments about 0.6% to about 1.75%. It has been found that the selected transparent overcoat can significantly reduce the haze from structures having a transparent conductive layer, and values for structures having an overcoat are conceivable for these ranges of haze values. Polymer overcoats are discussed above. A person of ordinary skill in the art will recognize that additional ranges of haze within the explicit ranges above are contemplated and are within the present disclosure.
[0057] It may also be desirable for the double-sided conductive structure to be essentially white, i.e., have little color. A color space may be defined to relate wavelengths of the spectrum to human color perception. CIELAB is a color space determined by the International Commission on Illumination (CIE). The CIELAB color space uses a set of three-dimensional coordinates, L*, a*, and b*, where L* refers to the lightness of the color, a* refers to the location of the color between red and green, and b* refers to the location of the color between yellow and blue. The "*" values represent normalized values relative to the standard white point. These CIELAB parameters may be determined using commercial software from measurements made with a spectrophotometer.
[0058] Based on the CIELAB parameters, essentially, a double-sided conductive structure with a suitable polymer substrate can be designed to obtain a moderate degree of whiteness, generally based on small absolute values of b* and a* on the CIELAB scale. In some embodiments, taking into account practical limitations, the design of the film can result in a whiter light within a certain desired range (absolute values of b* and a* lower than the target cutoff value), as achieved using nanoscale colorants. As further explained below, a moderate value of whiteness can be obtained by reducing the allowable range of total transmission of visible light. In some embodiments, the double-sided conductive structure can have a value of b* of about 4.0 or less, in further embodiments about 3.75 or less, and in other embodiments about 3.5 or less, although lower values can be achieved by appropriate selection of the substrate, which contributes the majority of the b* value.
[0059] The nanoscale colorant can be, for example, a nanoscale metal structure or a nanoscale pigment. Nanoscale metal structures generally have at least one average dimension that is about 100 nm or less. For example, nanoplates can have an average thickness of about 100 nm or less, and nanoribbons can have a thickness of about 100 nm or less and sometimes a width of about 100 nm or less. Metal nanoplates can be synthesized using solution-based techniques and their optical properties have been examined. Silver nanoplates with tailored absorption properties based on surface plasmon resonance are commercially available from nanoComposix, Inc., San Diego, CA, USA, Beijing Nanomeet Technology Co. Ltd., China, and Suzhou ColdStones Technology Co., Ltd., China. Larger scale synthesis of silver nanoplates is described in U.S. Pat. No. 10,147,512 to Hu et al., entitled "Methods for Synthesizing Silver Nanoplates and Noble Metal Coated Silver Nanoplates and Their Use in Transparent Films for Hue Control," which is incorporated herein by reference.
[0060] processing A processing method has been developed that allows for the reproducible formation of double-sided conductive structures with the thin dimensions described herein. In some embodiments, the structures are formed simultaneously on one side in a continuous manner. While one side is processed, the other side of the structure is typically supported on a release layer, such as the polymeric release layer described above. Processing can generally be conveniently conceptualized, but somewhat arbitrarily, into five components: 1) prepare the substrate for processing, 2) process the first side, 3) prepare the structure for processing the second side, 4) process the second side, and 5) complete the structure for shipping and / or storage.
[0061] When preparing and coating a structure, a substrate is obtained and provided with a release layer on one side, with the opposite surface exposed and coated. The substrate sheet is generally symmetrical, and either surface can be selected to be the first surface and processed. The release layer used to support and process the substrate should have suitable thermal stability for processing, which generally means that the melting point should be greater than approximately 180° C. For some polymer substrate materials, the glass transition temperature (T g ) may also be important. In some embodiments, T g It may be desirable for T to be at least about 100° C., and in further embodiments T g can be at least about 120° C. If the substrate supplier provides a substrate without a release layer or supported by a release layer that does not have the desired thermal stability, the substrate is placed on a suitable heat-stable release layer, and if appropriate, the initially provided release layer is removed to expose the first surface for coating. The substrate film on the heat-stable release layer is then ready for processing. Suitable release layer sheets are described above.
[0062] For embodiments having a hard coat, an undercoat can then be formed on the exposed surface. In some embodiments having a hard coat, the substrate supplier may provide a substrate that already has a hard coat such that the hard coat may be considered part of the substrate only from a process standpoint. Any suitable deposition method can be used for the deposition of the hard coat precursor solution, such as dip coating, spray coating, knife edge coating, bar coating, Mayer rod coating, slot coating, gravure printing, spin coating, etc. The deposition method dictates the amount of liquid deposited, and the concentration of the solution can be adjusted to provide the desired thickness of the product coating on the surface. After the dispersion forms the coating, the coating can be dried to remove the liquid and to properly crosslink. Drying can be done by any suitable method, such as exposure to ambient temperature, heating in an oven, blowing warm air over the coated structure, using heat lamps, or combinations thereof. Typically, the hard coat is crosslinked with ultraviolet light or heat, and a crosslinking initiator may or may not be used.
[0063] Whether or not a hard coat is applied, a thin metal conductive layer is then applied.
[0064] In some embodiments, a method is used to initially deposit a thin spread nanowire film, and further processing may or may not require fusing of the silver nanowires. As noted above, fusing into a single fused metal nanostructure network can provide improved properties of the transparent conductive film. Any suitable deposition method can be used for deposition of the metal nanowire ink, such as dip coating, spray coating, knife edge coating, bar coating, Mayer rod coating, slot die coating, gravure printing, spin coating, and the like. The ink can have properties, such as viscosity, appropriately adjusted with additives for the desired deposition method. Similarly, the deposition method can control the amount of liquid deposited, and the concentration of the ink can be adjusted to provide the desired loading of metal nanowires on the surface. After forming a coating with the dispersion, the thin spread metal conductive layer can be dried to remove the liquid.
[0065] The fusing of metal nanowires can be achieved by a variety of agents. Without wishing to be limited by theory, it is believed that the flux mobilizes the metal ions and the free energy is believed to be lowered in the fusing process. Excessive metal migration or growth can result in a decrease in optical properties in some embodiments, so the desired result is achieved by shifting the equilibrium in a reasonably controlled manner for a short period of time to produce sufficient fusing to obtain the desired electrical conductivity while maintaining the desired optical properties. In general, the fusing process can be performed by controlled exposure to fusing vapors and / or by the use of flux in solution. Under appropriate conditions, the fused metal conductive network is a monolithic structure.
[0066] In some embodiments, the initiation of the fusing process can be controlled by partial drying of the solution to increase the concentration of the constituents and quenching of the fusing process by, for example, completing washing or further drying of the metal layer. In some embodiments, subsequent processing by deposition of another ink results in the fusing of the metal nanowires into a fused metal nanostructured network that is electrically conductive. A fluxing agent can be introduced into the single ink along with the metal nanowires. One ink formulation for forming a single fused metal conductive network with thin, uniform metal nanowires is described in the examples below.
[0067] The metal nanowire layer can be dried, for example, with a heat gun, oven, thermal lamp, etc., although in some embodiments, a film that can be air dried may be desirable. In some embodiments, the film can be heated to a temperature of about 50° C. to about 150° C. during drying. Drying conditions can be designed to control the fusing process, but ink design can result in appropriate use of operating conditions readily available in conventional process equipment. After drying, the film can be washed one or more times, for example, with an alcohol, such as ethanol or isopropyl alcohol, or other solvent or solvent blend, to remove excess solids and reduce haze.
[0068] As described above, one or more overcoat layers can be applied over the thin metal conductive layer. The overcoat process is similar to the undercoat process described above using suitable substitutes for the coating solution. Patterning and other further processing after application of the overcoat is further described below.
[0069] After application of the overcoat and drying / curing of the overcoat on the first processed side, the overcoat can be covered by a release layer. The second side can remove the release layer to expose the second surface of the substrate and process the transparent conductive layer. The removal of the release layer from the second surface and the placement of the release layer on the first surface can be performed sequentially or nearly simultaneously. The sequential removal and placement of the release layer can generally be performed in either order, but it may be desirable to first place the release layer on the processed first layer to avoid moving the unsupported substrate through a conveyor system for a significant distance. Also, the sequential placement of the release layer on the first processed side of the substrate is consistent with then flipping the structure over and removing the release layer from the second surface while the second surface is facing up, which continues all processing relative to the facing surface. The simultaneous or nearly simultaneous performance of these operations can be interpreted by the eye of one skilled in the art as the components involved in these operations being in sufficient proximity so that their designs affect each other.
[0070] Once the second surface is exposed by removal of the release layer, the second surface can then be processed in the same manner as the first surface. In particular, if a hardcoat (undercoat) is desired and is not provided with the substrate, the hardcoat can be applied as described above. A thin metal conductive layer, typically by deposition and processing of a fused metal nanostructure network, can be deposited as described above. After the thin metal conductive layer is applied and dried and / or cured, an overcoat layer can then be applied and dried / cured as described above. After processing of the transparent conductive layer on the second side of the substrate is completed, a release layer can be used to cover this surface.
[0071] In some embodiments, processing is efficiently performed in a roll-to-roll fashion, where a roll of substrate is patterned and the processed structure is rolled up for further processing. Such roll-to-roll processing is compatible with commercial coating equipment and conveyors. To process the second side, the rolled up product with the first side coating can be turned around to unroll the rolled up structure and present the other surface to a coating head.
[0072] A schematic diagram of roll-to-roll processing of one surface of a substrate is shown in FIG. 4. Substrate supply roll 200 provides substrate sheet 202 that is conveyed through conveyor system 204. If substrate supply roll 200 provides substrate with initial release layer 206 on first surface 208 (where initial release layer 206 must be removed before further processing), initial release layer 206 can be separated from substrate sheet 202 and placed on initial release layer take-up roll 210. If process release layer 212 is placed on second surface of substrate sheet 202 to support substrate during processing, process release layer 212 can be dispersed from process release layer roll 214. Lamination rollers 216, 218 can be used to laminate process release layer 212 with substrate sheet 202, which may or may not require heat with moderate pressure. If substrate is provided on substrate supply roll 200 without initial release layer, there is no process to delaminate and roll up the initial release layer. Also, if the substrate is provided on the substrate supply roll 200 already with a process release layer, then a structure for providing the process release layer from a roll and lamination of the process release layer to the substrate is not required.
[0073] A substrate sheet 202 having a process release layer 212 can be prepared and a coating can be applied to a first surface 208 of the substrate sheet 202. If a hard-coat underlayer is applied, a hard-coat precursor solution can be applied in a first coater 230, such as a slot coater that applies a selected thin coating from a reservoir. Once the hard-coat precursor solution is applied, the substrate sheet 202 can proceed to a first coating processing station 232. The first coating processing station 232 can include a drying tool and / or a radiation source. The drying tool can provide heat to remove solvent and / or crosslink the polymer, and suitable drying tools include, for example, ovens, hot air blowers, heat lamps, and the like. Suitable radiation sources include, for example, ultraviolet lamps, electron beams, or other suitable radiation sources. The heat lamp can essentially provide the desired heat and radiation, such as infrared. For a UV-curable hard-coat, the radiation source can be an ultraviolet light source.
[0074] Regardless of whether a hardcoat undercoat is applied, the nanowire ink is coated onto the substrate sheet 202 with a second coater 240 to form a thin, spread, metallic conductive layer. After applying the nanowire ink, the substrate sheet 202 advances to a second coating processing station 242. The second coating processing station 242 can include a drying tool and / or a radiation source. Suitable drying tools and radiation sources are described for the first coating processing station 232 above and apply to the second coating processing station 242 as if written herein. If the nanowire ink includes a fusion solution, the resulting thin, spread, metallic conductive layer can include a fused metallic nanostructure network.
[0075] After the thin metal conductive layer is formed, the substrate sheet 202 travels through a conveyor system 204 to apply an overcoat layer. Specifically, a third coater 250 is used to apply an overcoat precursor solution onto the thin metal conductive layer. The conveyor system 204 then transports the substrate sheet 202 with the overcoat precursor solution to a third coating processing facility 252. The third coating processing facility 252 may include a drying tool and / or a radiation source. Suitable drying tools and radiation sources are described above for the first coating processing facility 232 and apply to the third coating processing facility 252 as if written herein. In an actual commercial roll-to-roll processing apparatus, the first coating processing facility 232 (if present), the second coating processing facility 242, and the third coating processing facility 252 may or may not be the same as each other for any pair out of the three, even though the range of possible designs is essentially the same for the three processing facilities.
[0076] After the overcoat is completed, if additional processing of the first surface 208 is not desired prior to processing the second surface on the other side of the substrate sheet 202, a second process release layer 260 can be delivered from a supply roll 262 and placed on top of the overcoat on the substrate sheet 202. The substrate 202 and the second process release layer 260 can be laminated with rollers 264, 266. The substrate sheet 202 can be placed on a storage roller 268 with the second process release layer 260 in place. If necessary, the first process release layer 212 can be removed prior to placing the process substrate sheet 202 on the storage roller 268, although this release of the first process release layer can be performed at the start of processing of the second surface. In another alternative embodiment, the substrate sheet 202 can be placed on the storage roller 268 without the second process release layer, and thus the supply roll 262 and rollers 264, 266 are not required. A second process release layer 260 can then be placed onto the substrate sheet 202 at the start of processing of the second surface.
[0077] In principle, the second layer can be processed without placing the substrate sheet 202 on the storage roller 268, but there are practical obstacles and this remains an option. It is generally undesirable to apply a coating to the underside due to gravity. Turning a moving substrate sheet over generally requires a significant amount of space or lateral stacking of process equipment. While these are not insurmountable obstacles, it is generally more convenient to place the substrate sheet 202 on the storage roller 268 and move the roll into position to process the second side. For example, the storage roll 268 can be turned over and placed in the position of the supply roll 200, with the substrate sheet then exiting from the top of the roll instead of the bottom. Appropriate processing can be performed to expose the second surface, which can be processed by supporting a second process release layer 260, which can be placed in place at the end of processing the first surface or at the start of processing the second surface. The second surface of the substrate sheet 202 can then be processed in the same manner as the first surface using the same or equivalent process components. Upon completion of processing of the second surface of substrate layer 202, the second surface may or may not be covered with a release layer, and the substrate sheet may or may not have been placed on a storage roll first. In either case, the double-sided coated substrate sheet is then ready for further processing into devices at the same location or at a separate location after shipping.
[0078] Touch sensors and corresponding processing Although the double-sided transparent conductive structure can be used for a variety of applications, the structure can be particularly useful for forming a touch sensor. Patterning can be performed for each side of the structure to form a desired conductive pattern for touch sensors and the like. In general, patterning can be performed by a variety of patterning techniques in the art. One commercial patterning method useful for touch sensors is based on ultraviolet laser ablation. The ultraviolet laser light has a wavelength that is absorbed by the substrate, and suitable ultraviolet lasers generally operate between 190 nm and 355 nm. Alternatively, photolithography can be used for patterning, where a light-sensitive composition, i.e., photoresist, is patterned by patterned illumination, e.g., through a mask, or by a direct-write lithography device. The latent image in the photoresist is developed to form a physical pattern, which is then transferred to the conductive layer.
[0079] Once the conductive layer is patterned, additional layers can be placed over the patterned conductive layer to introduce the structure into the device. A flexible photoconductive adhesive can be used to affix the patterned two-sided conductive structure to other structures along both surfaces. Suitable adhesive tapes are commercially available, for example, from Lintec Corporation (MO series); Saint Gobain Performance Plastics (DF713 series); Nitto Americas (LUCIACS CS9621T and LUCIAS CS9622T); LG Hausys OCA (OC9102D, OC9052D); DIC Corporation (DAITAC LT series OCA, DAITAC WS series OCA and DAITAC ZB series); PANAC Plastic Film Company (PANACLEAN series); Tesa SE (Germany) (AF61, 694 series, 696 series, and 697 series); Minnesota Mining and Manufacturing (3M, Minnesota USA - product numbers 8146, 8171, 8172, 8173, 1414-1, 9894, and similar products) and Adhesive Research (e.g. product 8932). Typically, metal traces can be connected along the edges of the pattern to the transparent conductive layer to provide final connection to the electrical circuitry.
[0080] With respect to the corresponding properties of multilayer films, the additional components are generally selected to have a small effect on the optical properties, and various coatings and substrates are commercially available for use in transparent elements.Suitable optical coatings, substrates and related materials are summarized above.Some of the construction materials can be electrically insulating, but when thicker insulating layers are used, the film can be patterned to provide contacts and electrical contacts to otherwise buried electrically conductive elements.
[0081] For the manufacture of sensors and the like, patterning is typically performed as outlined above to produce electrically conductive and electrically insulating regions, both of which are transparent. A schematic diagram of a layout of a portion of a touch sensor as viewed from above is shown in FIG. 3. Conductive lines D0-D4 are along one transparent conductive surface, and conductive lines S0-S4 are on the other transparent conductive surface of the structure. In some embodiments, an electrical signal can be induced along conductive line Dn and sensed along conductive line Sm when a touch is placed near the intersection of lines Dn and Sm. The capacitive response of the conductive lines is altered by the touch.
[0082] Stability and stability testing of transparent electrically conductive films In use, it is desirable for the transparent conductive film to last for a commercially acceptable period of time, such as the useful life of a corresponding device. The stabilized compositions and structures described herein serve this purpose, and the properties of the thinly spread metal conductive layer are well maintained. To test performance, accelerated aging procedures can be used to provide an objective evaluation over a reasonable period of time. These tests can be performed using commercially available environmental testing equipment.
[0083] The test chosen for use in the examples (Xenon test) was a black standard temperature of 60° C. (instrument settings), an air temperature of 38° C., a relative humidity of 50%, and 60 W / m 2 from a Xenon lamp using a daylight filter. 2The second accelerated wear test requires irradiance (300 nm to 400 nm) of 100 nm. Various suitable test equipment are commercially available, such as Atlas Suntest™ XXL equipment (Atlas Material Testing Solutions, Chicago, IL, USA) and SUGA environmental test equipment, Super Xenon Weather Meter, SX75 (Suga Testing Machine Co., Ltd., Japan). In the second accelerated wear test, the chamber temperature is set at 85° C., the relative humidity is set at 85%, and no lighting is used. Suitable equipment is commercially available for this high temperature and high humidity test, such as ESPEC Model BTL-433 environmental chamber (ESPEC Corp. North America, Inc. Hudsonville, MI, USA), and Thermotron SM-3.5-3800 Benchtop environmental chamber (Thermotron Inc., Holland, MI, USA). The following examples provide tests using two different laminate structures incorporating fused metal nanostructure networks, and the specific laminate structures are described below.
[0084] Under the test conditions specified in the previous paragraph, the samples can be evaluated by the change in sheet resistance as a function of time. The values are normalized to the initial sheet resistance and focus on the time evolution. Thus, in general, the time evolution is R t / R0, where R t is a measurement of the time-evolving sheet resistance, and R is the initial value of the sheet resistance. t The value of / R0 may be equal to or less than 1.8 after 1000 hours of environmental testing, equal to or less than 1.6 in further embodiments, equal to or less than 1.4 in further embodiments, and equal to or less than 1.2 after 500 hours in other embodiments. t The value of R may be less than or equal to 1.5 after about 1000 hours of environmental testing, in a further embodiment less than or equal to 1.5 after about 1500 hours, and in yet another embodiment less than or equal to 1.5 after about 2000 hours. tThe value of / R0 may be equal to or less than 1.2 after about 750 hours. t A person of ordinary skill in the art will recognize that additional ranges of / R0 and stability times are contemplated and are within the present disclosure. EXAMPLES
[0085] The optical properties of the transparent conductive film were examined for silver nanowires formed into a film in the dual coated structure described herein. The film was formed using Activegrid™ ink from C3Nano Inc. The processing details and structures are further described below.
[0086] Measurements were performed on the specific structures shown below. For the conductive structures, a transparent conductive film was formed using a silver nanowire ink essentially as described in Example 5 of the '968 patent cited above. The Activegrid™ product had silver nanowires with an average diameter of about 20-25 nm. The drying process in the roll-to-roll process described below causes chemical fusion as the solvent is removed to concentrate the components, where further reactions are terminated by continued drying. The amount of silver deposited is selected to target a film with a sheet resistance of either approximately 50 ohms / sq or 70 ohms / sq, as confirmed in the specific samples below. After the conductive film was dried, a commercial overcoat was slot coated onto the dried transparent conductive film in a roll-to-roll process. The overcoat was dried and crosslinked with a UV lamp to form an overcoat with a thickness of about 50-100 nm.
[0087] Optical and electrical property testing Sheet resistance, total transmission (TT), haze, and b* values for a series of examples were obtained. Sheet resistance (Ω / □) was measured by a four-point probe method, a contactless resistance meter, or by measuring the resistance of the film using a square defined by two (opaque) solid lines formed from silver paste. In some embodiments, a pair of parallel stripes of silver paste were applied onto the surface of the sample to define a square or rectangular shape, which was then annealed at approximately 120° C. for 20 minutes to cure and dry the silver paste. Alligator clips were connected to the silver paste stripes, and the leads were connected to a commercial resistance measurement device.
[0088] The total transmission (TT) and haze of the film samples were measured using a haze meter. The instrument is designed to evaluate optical properties based on the AS™ D1003 standard ("Standard Test Method for Haze and Luminous Transmittance of Transparent Plastics"), which is incorporated herein by reference. The total transmission and (transmittance) haze of these films include the substrate. The polyimide substrate used in Examples 1-4 and 6 has a total transmission of 91.5%, a haze in the range of 0.12% to 0.17%, and a b* in the range of 0.74 to 0.80. The substrate of Example 5 had similar optical properties. The CIELAB values of b* were determined using commercial software from measurements obtained with a Konica Minolta spectrophotometer CM-3700A with SpectraMagic™ NX software.
[0089] Reliability Testing Since it is desirable for the transparent conductive film to last for a commercially acceptable period of time, such as the useful life of a corresponding device, various accelerated aging tests can be used to provide an objective evaluation over a reasonable period of time. Specific tests were 65°C / 90% RH (relative humidity), 85°C / 85% RH, and xenon light tests, which are described in more detail below. These tests were conducted using commercially available environmental test equipment, which is referenced below.
[0090] Two tests were performed without lighting at 85° C. and 85% relative humidity or 65° C. / 90% RH. These tests are referred to as the 85C / 85% RH test or the 65C / 90% RH test, respectively.
[0091] Another test was performed with a black standard temperature of 60°C (instrument setting), an air temperature of 38°C, 50% relative humidity and 60 W / m from a xenon lamp using a daylight filter. 2 The test requires an irradiance of 100 nm to 400 nm. This test is called a xenon light test. Various suitable test instruments are commercially available, such as the Atlas Suntest™ XXL instrument (Atlas Material Testing Solutions, Chicago, IL, USA) and the SUGA Environmental Test Instrument, Super Xenon Weather Meter, SX75 (Suga Test Instruments Co., Ltd., Japan).
[0092] Under the test conditions specified in these tests, the samples can be evaluated by the change in sheet resistance as a function of time. The values can be normalized to the initial sheet resistance to focus on the time evolution. Generally, the time evolution is expressed as R / R0 or R t / R0, where R t is the time-evolving measured sheet resistance, and R0 is the initial value of the sheet resistance.
[0093] Preparation of test samples In the following examples, structures were made according to the process shown in Figures 5 and 6, which show the process for forming the test samples that are subjected to testing in the following examples. Referring to Figure 5, the coating of the first side of the substrate is shown diagrammatically. The substrate was provided with a polyethylene (PE) protective film. As shown in the first step of Figure 5, a PET film is laminated to the exposed side of the polyimide substrate before being placed in the coater. Two different polyimide (PI) substrates are examined in the following examples. As shown in the second step of Figure 5, the PE protective film is removed by peeling off the PE film, exposing the first surface for processing and applying an acrylate-based commercial hard coat to the substrate using slot coating, air drying and UV curing. After exposing the substrate surface for coating, the structure is placed in a coating apparatus. As shown in the next step of Figure 5, a conductive ink containing a solvent with a stable dispersion of silver nanowires (AgNWs), a polymer binder, and a fusing solution is applied to the cured hard coat using slot coating. The nanowire coating is air-dried (with heated forced air) to form a fused metallic nanostructure network. An acrylate overcoat solution is applied on top of the transparent conductive film using slot coating, then air-dried and subjected to UV curing. After the overcoat is cured, a PET protective film is laminated to the overcoat to form a release layer, as shown in the final step of Figure 5.
[0094] With reference to FIG. 6, the processing of the second side of the substrate is illustrated. The product of the first side of the substrate shown in FIG. 5 is wound up in a roll. To process the second side, the roll is turned over and processed by the same equipment used to coat the first side. In the first step of FIG. 6, the PET protective film covering the second surface of the substrate is peeled off to expose the second surface of the substrate. As shown in the second step of FIG. 6, an acrylate-based hard coat is applied to the exposed surface of the polyimide substrate using slot coating, and then the hard coat is air-dried and subjected to UV curing. As shown diagrammatically after the third step of FIG. 6, a conductive ink containing a solvent with a stable dispersion of silver nanowires (AgNWs), a polymer binder, and a fusing solution is applied to the cured hard coat, and then air-dried to form a fused metallic nanostructure network. Next, an overcoat precursor solution is applied on top of the transparent conductive film, which is then air-dried and subjected to UV curing. As shown in the final step of FIG. 6, a PE protective film is laminated on top of the cured overcoat.
[0095] Examples 1 and 2 These examples provide reliability test results under high temperature humidity test conditions or Xe irradiation conditions for samples having a hardcoat undercoat between the substrate and the bonded metal nanostructured network for two different optically transparent adhesives.
[0096] In Examples 1 and 2, samples were prepared as described above using a 13 micron polyimide substrate from Taimide, which is transparent in the visible spectrum and blocks UV radiation. The optical and electrical properties of the films were measured in duplicate and are listed in Table 1 below.
[0097] [Table 1]
[0098] Samples were also subjected to stability testing under two different test conditions using both high temperature / high humidity testing (85°C / 85%RH) and Xe irradiation testing. The 85°C / 85%RH test was performed using the structure shown in Figure 7. Referring to Figure 7, 125μm HC-PET film is applied to both sides of the structure using two different commercial optically clear adhesives: Example 1-LG9052D and Example 2-3M8146-2. Examples 1 and 2 include a hard coat between the polyimide substrate and the fused metal nanostructure network on both sides of the polyimide substrate. Using 85°C / 85%RH test conditions in a controlled test apparatus, the resistance (R / Ro) was measured as a function of time over 600 hours, and the time dependence of the resistance is shown in Figure 8.
[0099] In another set of tests, the samples were subjected to Xe light test conditions. Xe light test tests were performed in an Atlas Suntest™ XXL instrument using the structure of FIG. 9, which is the structure of FIG. 7 with half of its surface covered with black tape. Test instrument conditions were 60° C. black standard temperature (instrument settings), 38° C. air temperature, 50% relative humidity, and 60 W / m2 light from a xenon lamp using a daylight filter. 2 The irradiance (300 nm to 400 nm) was 100 nm. With reference to FIG. 9, unless otherwise noted, the hard-coated PET back cover sheet was placed facing up toward the device light and approximately half of the area was covered with black tape. For the Xe light test, R / Ro was measured over a 500-hour period and is shown in FIG. 10.
[0100] For Examples 1 and 2, all of the samples passed the test under the test conditions as determined by an R / Ro value of <1.1 at the end of the test period.
[0101] Examples 3 and 4 These examples test the reliability under test conditions for samples made without a hardcoat undercoat.
[0102] The coated substrates are prepared as described above for Examples 1 and 2, except that the placement of the hardcoat is omitted, and then the test structures are assembled. With reference to FIG. 11, the test specimens for Examples 3 and 4 were similar in construction to the specimens of Examples 1 and 2, except that no hardcoat was present (FIG. 7). A transparent conductive film is applied to both sides of the polyimide substrate, and an overcoat is applied to each side over the transparent conductive film. A PET protective film is applied on each side over the overcoat using two different optically clear adhesives: Example 3-LG9052D and Example 4-3M8146-2. Resistance (R / Ro) is measured over 600 hours using 85° C. / 85% RH test conditions and is shown in FIG. 12.
[0103] For xenon light testing, structures were formed as shown in Figure 13. Resistance (R / Ro) using Xe light test conditions was measured over 500 hours and the results are shown in Figure 14, where resistance as a function of test time is plotted. Accelerated testing was performed on an Atlas Suntest™ XXL instrument (Atlas Material Testing Solutions, Chicago, IL, USA). Test instrument conditions were 60°C black standard temperature (instrument settings), 38°C air temperature, 50% relative humidity, and 60 W / m2 from a xenon lamp using a daylight filter. 2 (300 nm to 400 nm). Unless otherwise noted, the hard-coated PET back cover sheet was placed face up towards the light of the device and approximately half of the area was covered with black tape.
[0104] For these samples, the R / Ro values under 85C / 85%RH test conditions did not remain below 1.2 until the end of the test. Under Xe test conditions, only the samples with OCA-B achieved the goal of maintaining R / Ro below 1.2. These examples demonstrate the usefulness of the hardcoat undercoating for these substrates.
[0105] Example 5 This example tests the reliability of a double-sided conductive structure having a thin polyimide substrate from an alternative source that does not use a hardcoat undercoat underneath the transparent conductor.
[0106] Samples of the double-sided conductive structures described above were fabricated using 15 micron thick transparent polyimide sheets from Kolon in a roll-to-roll process as described above. With reference to Figures 15 and 16, a transparent conductive film is applied to the Kolon CPI, an overcoat is applied over the transparent conductive film, and a PET protective film is applied over the overcoat using an optically clear adhesive (Flexible OCA from 3M). For Xe testing, black tape was applied over half of the top surface as shown in Figure 16.
[0107] Resistance (R / R0) using 65°C / 90%RH test conditions was measured over 800 hours and a plot of the time dependence is shown in Figure 17. Resistance (R / R0) using Xe light test conditions was measured over 1000 hours and is shown in Figure 18. Accelerated testing was performed on an Atlas Suntest™ XXL instrument (Atlas Material Testing Solutions, Chicago, IL, USA). Test instrument conditions were 60°C black standard temperature (instrument settings), 38°C air temperature, 50% relative humidity, and 60 W / m2 light from a xenon lamp using a daylight filter. 2 The test conditions were: 1) irradiance (300 nm - 400 nm) of 100 nm. Unless otherwise noted, the hard-coated PET back cover sheet was placed face up towards the light of the device and approximately half of the area was covered with black tape. A summary of the 65C / 90% RH and 85C / 85% RH tests is included in Table 2. Good test results were obtained for these samples without the use of a hard coat on the construction.
[0108] [Table 2]
[0109] Example 6 This example replicates the tests from Example 5 using the substrates of Examples 1-4.
[0110] Sample double-sided conductive structures shown in Figures 7 and 9 were fabricated using a 13 micron thick transparent polyimide sheet from Taimide using a roll-to-roll process as described above. The structures had a flexible optically clear adhesive from 3M Corporation.
[0111] The resistance (R / R0) using 65°C / 90%RH test conditions was measured over 800 hours and a plot of the time dependence is shown in Figure 19. The resistance (R / R0) using Xe light test conditions was measured over 1000 hours and is shown in Figure 20. Testing was performed as described in Example 5. The stability results are excellent.
[0112] The above embodiments are intended to be illustrative and not limiting. Further embodiments are within the scope of the claims. Moreover, although the present invention has been described with reference to specific embodiments, those skilled in the art will recognize that changes can be made in form and detail without departing from the spirit and scope of the present invention. Any incorporation by reference of the above documents is limited so as not to incorporate subject matter contrary to the explicit disclosure herein. Unless otherwise indicated, and as suggested in the discussion, to the extent that a particular structure, composition and / or process is described herein with components, elements, ingredients or other compartments, the disclosure herein should be understood to extend to specific embodiments, embodiments including specific components, elements, ingredients, other compartments or combinations thereof, as well as embodiments consisting essentially of such specific components, ingredients or other compartments or combinations thereof, which may include additional features that do not alter the basic nature of the subject matter.
Claims
1. a transparent polymeric substrate comprising a polymer and having a first surface and a second surface, said polymeric substrate having an average thickness of about 27 microns or less, said polymer in the form of said transparent polymeric substrate having a transmittance from 400 nm to 750 nm of at least about 88% and a transmittance over the UV spectrum from 330 nm to 375 nm of about 15% or less; a thin metallic conductive layer supported on each of the first and second surfaces of the transparent polymeric substrate; 1. A double-sided conductive structure comprising a polymer overcoat over each thin-spun metal conductive layer, the polymer overcoat having an average thickness of about 10 nm to about 200 nm; A double-sided conductive structure, each surface having a sheet resistance of about 120 Ohms / sq or less.
2. 10. The double-sided conductive structure of claim 1, further comprising a first hardcoat layer and a second hardcoat layer, each having an average thickness of about 50 nm to about 3 microns, wherein a first hardcoat layer is between the first surface of the transparent polymeric substrate and a first thinly spread metal conductive layer, and a second hardcoat layer is between the second surface of the transparent polymeric substrate, and both hardcoat layers comprise a crosslinked polyacrylate polymer.
3. 3. The double-sided conductive structure of claim 2, wherein each hardcoat layer has a thickness of about 100 nm to about 2.5 microns and comprises a highly crosslinked polyacrylate.
4. 4. The double-sided conductive structure of any one of claims 1 to 3, wherein the double-sided conductive structure can be assembled into a test structure having an optically transparent adhesive and a 125 micron thick PET film on each surface and subjected to an accelerated wear test at 85°C and 85% relative humidity for 500 hours with an increase in sheet resistance of about 1.20 or less.
5. The double-sided conductive structure of any one of claims 1 to 4, wherein the polymer comprises a polyimide.
6. The double-sided conductive structure of any one of claims 1 to 5, wherein the polymer substrate has an elongation of at least about 10%, a tensile strength of at least about 50 MPa, and a Young's modulus of about 1.5 GPa to about 7.0 GPa.
7. The double-sided conductive structure according to any one of claims 1 to 4, wherein the polymer comprises polysulfide, polysulfone, polyethylene naphthalate or polyethersulfone.
8. 8. The double-sided conductive structure of any one of claims 1 to 7, wherein each thinly spread metallic conductive layer comprises a fused metallic nanostructured network, the double-sided conductive structure can be repeatedly bent around a 1 mm diameter mandrel at least 200,000 times, and the sheet resistance of the conductive surface changes by 10% or less.
9. 10. The double-sided conductive structure of claim 8, wherein each deposited metal nanostructure layer has a sheet resistance of about 100 ohms / sq or less.
10. 10. The double-sided conductive structure of claim 9 having a visible light transmission of at least about 88%, a haze of about 2.5% or less, and a b* value of about 4.0 or less.
11. forming a thin, spread, metallic conductive layer supported on a first surface of a transparent polymeric substrate having an average thickness of about 27 microns or less, said polymeric substrate having a second surface supported on a first polymeric release film; applying a polymer overcoat over the first thin metallic conductive layer; placing a second polymeric release film over the polymeric overcoat; removing the first polymeric release film to expose the second surface of the transparent polymeric substrate; forming a second thin metallic conductive layer supported on the second surface of the transparent polymer substrate; applying a polymer overcoat over said second thin-film metal conductive layer.
12. 12. The method of claim 11, further comprising forming a crosslinked hardcoat layer having an average thickness of about 3 microns or less between the polymeric substrate and each of the first thin-layered metal conductive layer and the second thin-layered metal conductive layer.
13. 13. The method of claim 12, wherein forming the crosslinked hardcoat layer comprises irradiating with ultraviolet light to crosslink, and the crosslinked hardcoat comprises a polyacrylate.
14. The method of any one of claims 11 to 13, wherein the first polymeric release layer comprises a polymer sheet having a glass transition temperature of at least about 100°C.
15. The method of any one of claims 11 to 14, wherein each polymer overcoat is crosslinked with UV light.
16. forming the first thin-film metal conductive layer and the second thin-film metal conductive layer; applying a conductive ink comprising silver nanowires dispersed in a solvent and a polymer binder onto the first surface of the transparent polymer substrate; A method according to any one of claims 11 to 15, comprising drying the applied ink to form a thin spread metallic conductive layer.
17. The method of claim 16 , wherein the conductive ink includes a flux and the drying process forms a fused metal nanostructured layer.
18. a transparent polymeric film having an average thickness of about 27 microns or less; a thin metallic conductive layer on each side of said transparent polymer film; A transparent conductive film having an average thickness of about 30 microns or less, comprising a polymer overcoat over each thin-spread metal conductive layer, the polymer overcoat having an average thickness of about 10 nm to about 500 nm; the transparent conductive film having a sheet resistance of 100 Ohms / sq or less on each side, a %TT of at least 89%, a haze of 2.5% or less, and a b* of about 3.5 or less; A double-sided conductive structure can be assembled into a test structure with an optically clear adhesive (3M, 8146) and a 125 micron thick PET film on each surface and subjected to an accelerated abrasion test at 85° C. and 85% relative humidity for 500 hours, resulting in a transparent conductive film with an increase in sheet resistance of about 40% or less.
19. 20. The double-sided conductive structure of claim 18, further comprising a first hardcoat layer and a second hardcoat layer, each having an average thickness of about 50 nm to about 3 microns, wherein the first hardcoat layer is between the first surface of the transparent polymeric substrate and the first thin-splayed metal conductive layer, and the second hardcoat layer is between the second surface of the transparent polymeric substrate, and both hardcoat layers comprise a crosslinked polyacrylate polymer.
20. 20. The double-sided conductive structure of claim 19, wherein each hardcoat layer has a thickness of about 100 nm to about 2.5 microns and comprises a highly crosslinked polyacrylate.
21. 21. The double-sided conductive structure of any one of claims 18 to 20, wherein the double-sided conductive structure can be assembled into a test structure having an optically transparent adhesive and a 125 micron thick PET film on each surface and subjected to an accelerated wear test at 85°C and 85% relative humidity for 500 hours with an increase in sheet resistance of about 20% or less.
22. The double-sided conductive structure of any one of claims 18 to 21, wherein the polymer comprises a polyimide.
23. 23. The double-sided conductive structure of any one of claims 18 to 22, wherein the polymer substrate has an elongation of at least about 10%, a tensile strength of at least about 50 MPa, and a Young's modulus of about 1.5 GPa to about 7.0 GPa.
24. The double-sided conductive structure of any one of claims 18 to 21, wherein the polymer comprises polysulfide, polysulfone, polyethylene naphthalate, or polyethersulfone.
25. 25. The double-sided conductive structure of any one of claims 18 to 24, wherein each thinly spread metallic conductive layer comprises a fused metallic nanostructured network, the double-sided conductive structure can be repeatedly bent around a 1 mm diameter mandrel at least 200,000 times, and the sheet resistance of the conductive surface changes by 10% or less.
26. 26. The double-sided conductive structure of claim 25, wherein each deposited metal nanostructure layer has a sheet resistance of about 75 ohm / sq or less.
27. 27. The double-sided conductive structure of claim 26 having a visible light transmission of at least about 89%, a haze of about 2.5% or less, and a b* value of about 4.0 or less.